Insomnia and its Correlates in Migraine Patients with or without Aura - Khalid Al-Quliti (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: Few studies have investigated the correlates of insomnia severity level in a clinically diagnosed sample of migraine patients. This study explored associated factors of insomnia severity in a sample of Saudi Arabian patients with migraine headaches with/without aura (MA/MWA). Methods: This observational study used a cross-section design, and conveniently selected MA and MWA patients visiting outpatient department at general hospitals, Madinah, Saudi Arabia. The patients completed the Athens Insomnia Scale and an inventory to record sociodemographics and clinical data. Results: Insomnia was highly prevalent (50.6%) in both the MA/MWA patients. Being female (β = .25, p = .01), and overweight-obese (β = .19, p = .05) were associated with increasing insomnia severity. Most MA, and MWA patients were female (70.2%), were undergoing treatment for comorbid conditions (58.3%), and reported no habitual exercise or sports activities (57.1%). Discussion: A high prevalence of insomnia in the MA and MWA patients reinforces insomnia-migraine comorbidity. It may be useful to screen females and migraine patients who are obese for insomnia to better manage this comorbid epidemic.